(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The increasing contamination of water bodies due to industrial effluents, agricultural runoff, and domestic waste has necessitated the development of efficient and cost-effective water purification techniques. Adsorption has emerged as a promising method for the removal of a wide range of pollutants, including heavy metals, dyes, and organic compounds, due to its simplicity, versatility, and effectiveness. This paper reviews various adsorption techniques, focusing on the different adsorbents used, their properties, and their effectiveness in removing specific pollutants from water. The potential of novel adsorbents, such as biochar, carbon nanotubes, and metal-organic frameworks, is also discussed. The study concludes that while adsorption is a highly effective method for water purification, challenges such as adsorbent regeneration, pollutant selectivity, and large-scale implementation need to be addressed to enhance its practical application.